Prostate Cancer and Neuroendocrine Differentiation: More Neuronal, Less Endocrine? - Grigore, Alexandru Dan; Ben-Jacob, Eshel; Farach-Carson, Mary C. (Frontiers in Oncology, 2015)
Neuroendocrine differentiation (NED) marks a structural and functional feature of certain cancers, including prostate cancer, whereby the malignant tissue contains a significant proportion of cells displaying neuronal, endocrine, or mixed features. NED cells produce, and can secrete, a cocktail of mediators commonly ecountered in the nervous system, which may stimulate and coordinate cancer growth. In prostate cancer, NED appears during advanced stages, subsequent to treatment, and accompanies treatment resistance and poor prognosis. However, the term “neuroendocrine” in this context is intrinsically vague. This article seeks to provide a framework on which a unified view of NED might emerge. First, we review the mutually beneficial interplay between prostate cancer and neural structures, mainly supported by cell biology experiments and neurological conditions. Next, we address the correlations between prostate cancer and neural functions, as described in the literature. Based upon the integration of clinical and basic observations, we suggest that it is legitimate to seek for true neural differentiation, or neuromimicry, in cancer progression, most notably in prostate cancer cells exhibiting what is commonly described as NED.